2014
DOI: 10.1093/jjco/hyt203
|View full text |Cite
|
Sign up to set email alerts
|

Soy Intake and Breast Cancer Risk: An Evaluation Based on a Systematic Review of Epidemiologic Evidence Among the Japanese Population

Abstract: Objective:We reviewed epidemiological studies of soy intake and breast cancer among Japanese women. This report is one among a series of articles by our research group, which is evaluating the existing evidence concerning the association between health-related lifestyles and cancer. Methods: Original data were obtained from MEDLINE searches using PubMed or from searches of the Ichushi database, complemented with manual searches. Evaluation of associations was based on the strength of evidence and the magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 34 publications
0
51
0
Order By: Relevance
“…However, unlike the carcinogenic potential of steroidal estrogens the epidemiology literature (Chen et al , 2014, Nagata et al , 2014, Wu et al , 2008) supports the view that soy diet can reduce the risk of breast cancer. However, in western society this has been translated into the use of soy in adulthood to prevent breast cancer.…”
Section: Clinical Consequences Of Estrogen Deprivationmentioning
confidence: 99%
“…However, unlike the carcinogenic potential of steroidal estrogens the epidemiology literature (Chen et al , 2014, Nagata et al , 2014, Wu et al , 2008) supports the view that soy diet can reduce the risk of breast cancer. However, in western society this has been translated into the use of soy in adulthood to prevent breast cancer.…”
Section: Clinical Consequences Of Estrogen Deprivationmentioning
confidence: 99%
“…However, the clear beneficial effects of these estrogens remain controversial. Several meta-analysis (11)(12)(13) that assessed soy exposure and breast cancer risk revealed that studies conducted in Asian countries showed a significant trend of a reduced risk with increased soy intake in both pre-and postmenopausal Asian women. On the other hand, no association was observed between soy consumption and breast cancer risk in low soy consuming Western populations (11,13), suggesting that consumption of soy products in amounts taken in the Asian population may have protective benefits.…”
Section: Introductionmentioning
confidence: 99%
“…The protective effect of dietary soy intake against bca has been demonstrated by a number of studies in Asia. A systematic review from Japan showed that soy intake is associated with a lower risk of female bca (or: 0.5-0.67) 44 . A meta-analysis from China Categorized as higher or lower than the mean of the intake by control subjects (7.84 mg/day).…”
Section: Discussionmentioning
confidence: 99%